Tinjauan Hukum Siyasah terhadap Kebijakan Publik dalam Penanganan Lingkungan Hidup - Dwi Wijayanti; Samsul Munir; Nurul Syalafiyah (Bahasa Indonesia, 2024)
Public policy in environmental management is a crucial aspect of achieving sustainable development. From the perspective of fiqh siyasah, the government holds the responsibility to formulate and implement effective policies to protect and manage the environment. This study analyzes the siyasah law review of public policy in environmental management in Indonesia. The method used is a literature study by analyzing various Islamic legal sources and related regulations. The results indicate that the principles of fiqh siyasah support the active role of the government in preserving environmental sustainability through fair regulations and strict law enforcement. Implementing policies aligned with Islamic values can enhance public awareness and the effectiveness of environmental management.